Draft Annual Plan 1982-83 Volume II Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1982)
In pursuant of the new policy of development and growth in rural areas through integrated intra and inter sectoral approach, great responsibility vests on the planners and executors in this rural sector. As Agriculture happens to be the basic vocation involving of over two third of the population in the country and maximum population in Arunachal Pradesh, the entire programme has to-be oriented and geared towards stepping up crop production, making full use of inputs, infrastructure, technology and extension net work.
Government of Arunachal Pradesh, Planning and Development Department